2017
DOI: 10.1002/1878-0261.12116
|View full text |Cite
|
Sign up to set email alerts
|

Loss of AMPK activation promotes the invasion and metastasis of pancreatic cancer through an HSF1‐dependent pathway

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a lethal malignancy with a mortality rate that closely parallels its incidence rate, and a better understanding of the molecular and cellular mechanisms associated with the invasion and distant metastasis is required. Heat shock factor 1 (HSF1) is a very highly conserved factor in eukaryotes that regulates the protective heat shock response. Here, we show that HSF1 is abnormally activated in pancreatic cancer. The knockdown of HSF1 impaired the invasion and migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 55 publications
8
63
0
Order By: Relevance
“…Indeed, it was demonstrated that HSF1 promotes TGFβ-induced EMT, tumorigenesis, and metastases in a murine breast cancer model [161]; the EMT-promoting mechanism was due to HSF1-mediated stimulation of the RAS/RAF/MEK/ERK1/2 signaling pathway. Additionally, HSF1 was found to be required for EMT in ovarian cancer (including a spheroid growth model) [162], hepatocellular carcinoma [163], and pancreatic cancer [164]. In the latter case, the abnormal HSF1 activation (phosphorylation) resulting in EMT induction in pancreatic cancer cells was correlated with the failure of AMPK activation in pancreatic tumors [164].…”
Section: Hsf1 and Hsf1-activating Exposurementioning
confidence: 99%
“…Indeed, it was demonstrated that HSF1 promotes TGFβ-induced EMT, tumorigenesis, and metastases in a murine breast cancer model [161]; the EMT-promoting mechanism was due to HSF1-mediated stimulation of the RAS/RAF/MEK/ERK1/2 signaling pathway. Additionally, HSF1 was found to be required for EMT in ovarian cancer (including a spheroid growth model) [162], hepatocellular carcinoma [163], and pancreatic cancer [164]. In the latter case, the abnormal HSF1 activation (phosphorylation) resulting in EMT induction in pancreatic cancer cells was correlated with the failure of AMPK activation in pancreatic tumors [164].…”
Section: Hsf1 and Hsf1-activating Exposurementioning
confidence: 99%
“…Interestingly, we found that EF inactivated AMPK signaling, which was related to CD9 expression in keratinocytes. It has been indicated that AMPK pathway is involved in cell migration in many types of cancer cells [19,31], and previous study has confirmed that the inhibition of AMPK promotes the mobility of HaCaT cells [17]. Furthermore, hypoxic preconditioning also promotes the migration of keratinocytes through AMPK pathway [32,33].…”
Section: Discussionmentioning
confidence: 89%
“…Studies have shown that the activation of AMPK inhibits the migration of tongue squamous cell carcinoma cells [18]. Loss of AMPK activation promotes the invasion and metabolism in many cancers [15,19]. Recently, an AMPK activator met has been shown to reduce cell proliferation and delay wound healing [20], suggesting that AMPK may be involved in the cytobiology of keratinocytes during wound repair.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate whether MA affects the viability of GBC cells, NOZ and GBC-SD cells were incubated with a series of incremental doses of MA (0, 1, 2, 4, 6, 8, 12 and 16 μmol/L) to determine whether the effects are time-dependent. The cell viability was analysed by the assessment of the absorbance at 490 nm after 24,48 and 72 hours using the MTT assay. As shown in Figure 1A,B, MA repressed the growth of GBC cells in a time-and dose-dependent manner.…”
Section: α-Mangostin Suppresses Proliferation and Induces Apoptosismentioning
confidence: 99%